Development Of Framework To Engage Student's Learning In Technical MOOC Using Wearable Technology - Ahmad Fesol., Siti Feirusz (2019)
The low completion rate issue in MOOC has become one of the main highlights by researchers. It is reported that only 10 to 15 per cent of the students able to complete the MOOC. This low completion rate was due to the students are less engaged with the MOOC content causing them to demotivate to complete the whole MOOC. Engaging students in a MOOC environment especially for non-technical subjects was achievable. However, for a technical MOOC it involved significant challenges. Researches highlighted that one of the requirements for designing an engaging practice-based MOOC or technical MOOC is to include practice-oriented learning mode into its course structure. Therefore, the aim of this study is to develop a framework to engage student’s learning in technical MOOC using wearable technology. This study adopted the case study methodology approach with qualitative and quantitative analysis which conducted at UTeM. The instruments used in this study include technical MOOC, wearable technology, and student engagement items. A total of 375 engineering students involved in this study and the data were analysed using descriptive and parametric testing. The survey results reflected that the learning materials produced by wearable technology do contribute towards positive effect in increasing the level of student’s engagement with the learning process. Among key recommendations for future study are to implement the proposed framework to design and develop other engineering and technical courses and to further explore other potential elements of wearable technology to enhance student engagement in online learning.